2013
DOI: 10.2174/1871530311313020001
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Parathyroid Hormone Levels Despite Persistent Hypocalcemia in Patients with Kidney Failure Recovering from Septic Shock

Abstract: The systemic inflammatory response syndrome probably leads to inappropriately high Parathyroid hormone levels during septic shock. In the recovery phase, Parathyroid hormone levels decrease, but calcium levels remain low, displaying evidence that the parathyroid is not responding as expected. Since Parathyroid hormone receptors and calcium-sensing receptors have been described in immune cells and other cell types, we propose that these effects may have a plethora of other deleterious effects, with important im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…We also showed that 84 % of our patients presented a blunted parathyroid response to decreased circulating vitamin D. This result is in agreement with a recent study in critically ill children with sepsis [ 39 ]. However, studies in critically ill adults with or without sepsis have supported an elevated PTH, contrary to our findings [ [40] , [41] , [42] ]. In a pilot study of 37 critically ill patients, Carlstedt et al found increased PTH that was associated with the severity and a poor outcome [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…We also showed that 84 % of our patients presented a blunted parathyroid response to decreased circulating vitamin D. This result is in agreement with a recent study in critically ill children with sepsis [ 39 ]. However, studies in critically ill adults with or without sepsis have supported an elevated PTH, contrary to our findings [ [40] , [41] , [42] ]. In a pilot study of 37 critically ill patients, Carlstedt et al found increased PTH that was associated with the severity and a poor outcome [ 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, parathyroid hormone (PTH) is often elevated in acute inflammation such as septic shock (55), sepsis (56), or after endotoxin injection (57), but levels are normal, high, or low in chronic inflammation (5862). Catabolic effects of PTH on bone might be largely determined by parallel inflammation (6) or by an increase in parallel glucocorticoids (63).…”
Section: Other Pathways Of Inflammation-stimulated Bone Lossmentioning
confidence: 99%